2022
DOI: 10.3390/ijms23084148
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker of Neuroinflammation in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is caused by abnormal accumulation of α-synuclein in dopaminergic neurons of the substantia nigra, which subsequently causes motor symptoms. Neuroinflammation plays a vital role in the pathogenesis of neurodegeneration in PD. This neuroinflammatory neurodegeneration involves the activation of microglia, upregulation of proinflammatory factors, and gut microbiota. In this review, we summarized the recent findings on detection of PD by using inflammatory biomarkers, such as interleukin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 179 publications
0
65
0
Order By: Relevance
“…While Hs-CRP level is a generic measure of inflammation, several studies have shown that they are useful for screening and monitoring response to treatment in various neurological diseases such as stroke, dementia, and others. 5 , 21 , 23 As such, we think that our findings highlighting the utility of common blood biomarkers in PD will be clinically useful. Ideally, we could have analyzed additional more neuro specific markers (such as neurofilament light chain) to see if these also yield similar results.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…While Hs-CRP level is a generic measure of inflammation, several studies have shown that they are useful for screening and monitoring response to treatment in various neurological diseases such as stroke, dementia, and others. 5 , 21 , 23 As such, we think that our findings highlighting the utility of common blood biomarkers in PD will be clinically useful. Ideally, we could have analyzed additional more neuro specific markers (such as neurofilament light chain) to see if these also yield similar results.…”
Section: Discussionmentioning
confidence: 66%
“…While Hs-CRP level is a generic measure of inflammation, several studies have shown that they are useful for screening and monitoring response to treatment in various neurological diseases such as stroke, dementia, and others. 5,21,23 As such, we think that our Figure 3. Absolute spectral power of frequency bands on regional distribution showed with topographic map and peak frequency of occipital derivation showed with cures in different groups.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…While the causes associated with neuronal impairment remain poorly understood, increasing evidence proved systemic inflammatory response especially neuroinflammation is crucial in the progression of neurodegenerative diseases [1,2]. The core of neuroinflammation is likely the same in aging, metabolic diseases such as hypertension and diabetes, or cerebral insults such as stroke and injury [3], and inflammatory mediator tumor necrosis factor-α (TNF-α) was proved to serve as a key player and biomarker of neuroinflammation [4]. Speaking of molecular mechanisms, plenty of evidence suggested that the aggregation of β-amyloid, αsynuclein, and Tau protein plays a crucial role in neurodegenerative cascades [5][6][7].…”
Section: Introductionmentioning
confidence: 99%